2010
DOI: 10.1101/cshperspect.a001925
|View full text |Cite
|
Sign up to set email alerts
|

Initiating and Growing an Axon

Abstract: The ability of neurons to form a single axon and multiple dendrites underlies the directional flow of information transfer in the central nervous system. Dendrites and axons are molecularly and functionally distinct domains. Dendrites integrate synaptic inputs, triggering the generation of action potentials at the level of the soma. Action potentials then propagate along the axon, which makes presynaptic contacts onto target cells. This article reviews what is known about the cellular and molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
133
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 174 publications
5
133
1
1
Order By: Relevance
“…Several initial candidates for downstream targets failed our tests of involvement. Although contact mediated cues are important for axon outgrowth and branching (for review, see Polleux and Snider, 2010;Raper and Mason, 2010), we found no evidence for structural alterations in the AIS, branching pattern, axonal length, or cholesterol content that can readily explain the strong propagation changes. Furthermore, although axon-specific potassium channels are prime candidates to explain the severe disruption of axonal signal propagation, we found no evidence for alterations in a putative axon-specific, principal-neuron potassium channel, K v 7.2/3.…”
Section: Discussioncontrasting
confidence: 59%
“…Several initial candidates for downstream targets failed our tests of involvement. Although contact mediated cues are important for axon outgrowth and branching (for review, see Polleux and Snider, 2010;Raper and Mason, 2010), we found no evidence for structural alterations in the AIS, branching pattern, axonal length, or cholesterol content that can readily explain the strong propagation changes. Furthermore, although axon-specific potassium channels are prime candidates to explain the severe disruption of axonal signal propagation, we found no evidence for alterations in a putative axon-specific, principal-neuron potassium channel, K v 7.2/3.…”
Section: Discussioncontrasting
confidence: 59%
“…Axonal outgrowth is a coordinated process of cytoskeletal reorganization and membrane transport (Tang, 2001;Arimura and Kaibuchi, 2007;Polleux and Snider, 2010). This process has been extensively investigated, and a number of molecules involved in neurite outgrowth have been delineated in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Neither axon formation nor polarity was affected by knockdown or knockout of LMTK1. Several molecules with axonal outgrowth activity determine polarity rather than regulate axon length itself (Polleux and Snider, 2010), but LMTK1 is not a polarity-establishing protein. Because total neurite length did not change after the overexpression of LMTK1-S34A or the knockdown of LMTK1, axons were lengthened at the expense of the elongation of other neurites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of these two neuronal compartments is essential for correct neuronal function, and occurs soon after the neuron is born. Growing evidence, primarily from in vitro studies, suggests that regulation of the microtubule cytoskeleton provides key instructive signals to specify axon and dendrite identity (Polleux and Snider, 2010). In addition to their role in neuronal polarity during development, microtubule dynamics have been recently implicated in axonal regeneration and degeneration (reviewed in chapter 1).…”
Section: Introductionmentioning
confidence: 99%